2018
DOI: 10.14302/issn.2328-0182.japst-18-2344
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantification of an Adulterant in a Dietary Supplement Marketed for Sexual Enhancement

Abstract: In recent years, the consumption of dietary supplements (DS) has increased worldwide. In Argentina, approximately 14 million DS units were sold between 2015 and 2017. The adulteration of DS with active pharmaceutical ingredients or their analogues has been reported. This represents an alarming emerging risk to public health. The aim of this work was to detect the possible adulteration of a DS marketed in Argentina for the treatment of erectile dysfunction. Initially, thin layer chromatography analysis of the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…This study represents the first report in Latin America and one of the few independent studies of an adulteration with an unapproved PDE‐5i of a DS for the treatment of ED 26 . Recently, we have also reported the identification and quantification, using HPLC‐tandem mass spectrometry (MS/MS), of tadalafil as an adulterant in a DS marketed in Argentina for sexual enhancement 27 . Mustazza et al 28 detected the presence of sildenafil analogues in an illegal supplement, but more importantly the authors also reported extensive spectral data on mass fragmentation and NMR chemical shifts of sildenafil, thiosildenafil, acetildenafil, and 13 of their analogues, and provide comprehensive information on the route of synthesis for the benefit of those laboratories that need to synthesize analogue reference standards in‐house.…”
Section: Resultsmentioning
confidence: 80%
“…This study represents the first report in Latin America and one of the few independent studies of an adulteration with an unapproved PDE‐5i of a DS for the treatment of ED 26 . Recently, we have also reported the identification and quantification, using HPLC‐tandem mass spectrometry (MS/MS), of tadalafil as an adulterant in a DS marketed in Argentina for sexual enhancement 27 . Mustazza et al 28 detected the presence of sildenafil analogues in an illegal supplement, but more importantly the authors also reported extensive spectral data on mass fragmentation and NMR chemical shifts of sildenafil, thiosildenafil, acetildenafil, and 13 of their analogues, and provide comprehensive information on the route of synthesis for the benefit of those laboratories that need to synthesize analogue reference standards in‐house.…”
Section: Resultsmentioning
confidence: 80%
“…In Romania, the National Agency for Medicine and Medical Devices of Romania (NAMMDR) lists sildenafil medicinal products of the following therapeutic strengths: 25, 50, and 100 mg. The adverse effects related to sildenafil consumption include headache, flushing, dizziness, dyspepsia, nasal congestion, and altered vision [ 4 , 5 , 6 ]. Furthermore, disturbed color vision and temporary effects on the electroretinogram (ERG) were reported [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This practice of adulterating food supplements for both potency and losing weight is a common phenomenon worldwide [ 4 ]. Moreover, the risk of harm is increased by adding synthetic drugs and various impurities [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations